Common presenting issues in psychotherapeutic practice - Douglas, Barbara
Learning how to work effectively with a broad range of clients and their presenting issues is a vital part of a career as a therapist, but engaging with the often conflicting worlds of descriptive psychopathology and the subjective meanings of the therapist and client is a real challenge for trainees. They have to develop the skills and knowledge that allow both approaches, one medical, one humanistic, to work successfully together. This book helps students to confidently do just that, proving a comprehensive introduction to the theory, research and practice behind a range of common presenting issues. Key issues covered include: anxiety, depression, trauma, bipolar disorder, psychosis, eating disorders, borderline personality disorder. This book should be on the desk of every counselling, psychotherapy and counselling psychology trainee, and is recommended reading for other practitioners of health and social care working with these common presetting issues - -